PENGARUH PEMBENAH TANAH HAYATI TERHADAP SIFAT KIMIA ENTISOL TERGENANG DAN TIDAK TERGENANG - Widyantoro, Arief; Sambodo, Anandeya Satrio; Rahayu, Sariman Karta; Supriyanto, Supriyanto (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Farmers began to implement organic systems when the quality of rice fields decreased. Indonesia has several active volcanoes so that the agricultural land was formed by generally Entisols. Several natural and synthetic soil conditioners were starting to be used to decompose the litter and increase the availability of Entisol nutrients. The research aimed to study the effect of providing biological soil amendments on the chemical properties of Entisols. The demonstration plots scale research were used a completely randomized design with a combination of treatments: (P1) Flooded dolomite control, (P2) Non-flooded dolomite control, (P3) Flooded bio soil-neutralizer, and (P4) Non-flooded bio soil-neutralizer. Parameters of soil chemical properties observed were pH, C-organic (%), N-total (%), P2O5-total (%), K2O-total (%), CEC (c mol + kg-1), total bacteria (CFU mL-1), and total fungi (spores g-1). The chemical properties of Entisols before treatment showed slightly acidic pH, low C-organic, low N-total, low K-total, low P-total, and very high CEC. After applying the soil neutralizer, there were an increase in chemical properties including pH becoming alkaline and neutral, medium C-organic, standards to moderat NPK-total, and high CEC. Flooding treatment did not increase the chemical properties of the Entisols.